Making better biomass - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Increasing the efficiency and cleanliness of charcoal is a key area of research in renewable energies. Extensively used in cooking and heating, it is often a household s prime source of energy, and is preferable to the burning of wood.The challenge...